Mucormycosis medications: a patent review. (2nd November 2021) - Imran, Mohd.; A.S., Alshrari; Tauseef, Mohammad; Khan, Shah Alam; Hudu, Shuaibu Abdullahi; Abida,
ABSTRACT: Introduction: Mucormycosis is an uncommon but life-threatening infection with nonspecific clinical manifestations that make its diagnosis/treatment difficult. The current literature indicates that mucormycosis case incidences are on the rise in developing and developed countries, and, unfortunately, there are only a few treatments available. Accordingly, it is essential to provide more treatment options for mucormycosis. Area Covered: This patent review focuses on the granted patents and patent applications related to medication for mucormycosis treatment from the publication year of the amphotericin-B patent application (1958) till 30 January 2021. Expert Opinion: Mucormycosis has few available treatments, including amphotericin-B, isavuconazonium sulfate, posaconazole, or their combination. A few anti-mucormycosis medicines are under clinical development. The exact burden of mucormycosis is unknown, but it is expected to be higher than the reported cases because of mucormycosis epidemiological changes. This patent review has shown that scientists are progressing toward developing a new treatment for mucormycosis in the form of new chemical compounds, new drug combinations, and dosage forms, vaccines, plant products, drug repurposing, and derivatives of the biomolecules. This progress is encouraging to fight this devastating illness.